Pemeliharaan Tahunan Pressure Transmitter Area Steam Generation Industri Petrokimia di PT. X - Hafiz, Muhammad; Novan Akhiriyanto (Elposys: Jurnal Sistem Kelistrikan, 2025)
Monitoring steam generation systems in the petrochemical industry is essential because small pressure changes can significantly affect product quality and pose safety risks. This study focuses on calibrating the Endress+Hauser Cerabar M PMC41 pressure Transmitter at PT. X, a leading Indonesian fatty alcohol and oleochemical producer. Calibration was performed to ensure accurate pressure measurement of steam generation processes using a zero calibration technique to correct reading Errors. Measurement data were collected before and after calibration at 0%, 25%, 50%, and 100% pressure levels. The initial Error in pressure measurement was 31.799 bar (4.47%), while the current output Error was 16.76 mA (3.8%). After calibration, these Errors reduced to 30.266 bar (0.72%) and 16.023 mA (0.115%), respectively. These results indicate a significant improvement in the Transmitter’s performance, aligning with the International Electrotechnical Commission (IEC) No. 13B-23 standards. The calibration process effectively minimized measurement Errors, ensuring precise monitoring of pressure parameters in the steam generation system and maintaining operational stability. Accurate pressure control is crucial to optimizing production efficiency and maintaining safety standards at PT. X.